Design of Voltage Balancing Circuit for Power Batteries in New Energy Vehicles - Liu, Yiwen; Zhou, Rui; Hong, Shiyun; Han, Siyu; Pan, Jiawen (International Journal of Natural Resources and Environmental Studies, 2026)
Aiming at the issue of inconsistent cell voltages in series-connected power battery packs for new energy vehicles, this paper investigates voltage balancing circuits, with the goal of preventing the degradation of overall battery pack performance and service life caused by this problem. The study investigates a passive balancing circuit using resistors as energy dissipation components and an active voltage balancing circuit employing capacitors as energy storage and transfer devices. Simulation analyses of both balancing circuits are carried out in the MATLAB environment. The results demonstrate that the single-capacitor method exhibits distinct advantages in terms of energy efficiency, balancing speed, and system reliability, thus providing a more advanced and practical solution for voltage balancing of power batteries in new energy vehicles.